Does a Cognitive Conflict-Based Physics Website Integrated with Augmented Reality and STEM Improve Critical Thinking and Remediate Misconceptions on Two-Dimensional Motion? - Indah Zalsabila; Fatni Mufit; Emiliannur Emiliannur; Hidayati Hidayati; Yeka Hendriyani; Zahra Fathanah (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Critical thinking and conceptual understanding are essential competencies in physics learning, yet students still experience low critical thinking skills and high levels of misconceptions, particularly in two-dimensional motion topics. This research sought to evaluate the extent to which an augmented reality (AR) and STEM integrated cognitive conflict-based physics website contributes to the development of critical thinking skills and the correction of misconceptions in two-dimensional motion concepts. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent pretest-posttest control group design. The participants were 63 tenth-grade students of SMAN 2 Lubuk Sikaping, including 32 students in the experimental group and 31 students in the control group. A validated and reliable four-levels multiple-choice test was employed to collect data on critical thinking abilities and misconceptions concurrently. Descriptive statistics and the Mann–Whitney U test were employed to analyze the collected data. The results showed that the experimental class achieved a higher mean posttest score in critical thinking skills (64,3) than the control class (39,1). The Mann–Whitney test showed a significant difference between the two groups (p < 0.05). In addition, the percentage of misconceptions in the experimental class decreased from 80.0 to 46.0, while the control class showed only a slight reduction. The results of the study show that the AR-STEM integrated cognitive conflict-based physics website effectively improves critical thinking skills and corrects misunderstandings in two-dimensional motion learning. Therefore, the website can serve as an innovative learning resource to support meaningful physics learning and conceptual change.